Process of parturition in female mithun (Bos frontalis) - AHMED, F A; BAISHYA, N; BUJARBARUA, K M; AKHTAR, F (The Indian Journal of Animal Reproduction, 2023)
The present investigation was carried out on 12 parous female mithun (Bosfrontalis) maintained at National Research Centre on Mithun, Jharnapani, Nagaland. The first, second and third stages of parturition required a mean duration of 156.17 ±46.71 (range 90-242 min.), 71.52 ± 18.82 (range 48-105 min.) and 199.65 ± 54,75 (range 145 - 318 min.) minutes, respectively. Tlte mean duration for the whole act of parturition was recorded to be 427.33 ± 74.48 (range 310 - 560 min.) minutes. In all the cases, allantochorion appeared as the first water bag. The fetuses were found_ in anterior longitudinal presentation and dorso-sacral position with the ead resting on forelimbs. Maxitnum number of calving (62.96%) occurred during night hours (in between 6.00 PM and 6.00 AM).